2000
DOI: 10.1128/mcb.20.7.2385-2399.2000
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Core Promoter Recognition Caused by Novel Yeast TAF145 Mutations Can Be Restored by Creating a Canonical TATA Element within the Promoter Region of the TUB2Gene

Abstract: The general transcription factor TFIID, which is composed of TATA-binding protein (TBP) and an array of TBP-associated factors (TAFs), has been shown to play a crucial role in recognition of the core promoters of eukaryotic genes. We isolated Saccharomyces cerevisiae yeast TAF145 (yTAF145) temperature-sensitive mutants in which transcription of a specific subset of genes was impaired at restrictive temperatures. The set of genes affected in these mutants overlapped with but was not identical to the set of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(104 citation statements)
references
References 107 publications
6
96
2
Order By: Relevance
“…11). Promoter swapping experiments demonstrated that TAF145 function is demanded by the core promoter region rather than by upstream activating sequences (UASs) as examined for the CLN2, RPS5, and TUB2 genes (19,20). Thus, it appears that TAF145 function is tightly connected to core promoter recognition, in accordance with human TAF250, which directly recognizes an initiator element as described above (13).…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…11). Promoter swapping experiments demonstrated that TAF145 function is demanded by the core promoter region rather than by upstream activating sequences (UASs) as examined for the CLN2, RPS5, and TUB2 genes (19,20). Thus, it appears that TAF145 function is tightly connected to core promoter recognition, in accordance with human TAF250, which directly recognizes an initiator element as described above (13).…”
mentioning
confidence: 78%
“…The yeast strains used in this study, YTK3010 (wild type), YTK3002 (Y570N), YTK3003 (N568⌬), and YTK3005 (T657K) were generated by plasmid shuffle techniques from the parental strain Y22.1 (20). They carry a deletion of the chromosomal TAF145 coding region and the wild type or mutant TAF145 gene on a TRP1-based low copy number vector (20).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TFIID comprises the TATA box-binding protein (TBP) and about 12 TBP-associated factors (TAF II s). Although referred to as general transcription factors, distinct TAF II proteins seem to be recruited selectively by specific promoters and are, therefore, essential for the transcription of a subset of genes (Albright & Tjian, 2000;Tsukihashi et al, 2000;Li et al, 2002;and references therein). In addition to these general transcription factors, sequence-specific DNA-binding transcription factors, co-activators and chromatin-remodelling proteins are required to ac2tivate transcription (reviewed by Näär et al, 2001).…”
Section: Introductionmentioning
confidence: 99%